Remote Plasmas Chemical Vapour Deposition and Reactive Sputtering in Magnetron Plasmas - André Ricard; Thierry Belmonte; Thierry Czerwiec; Stephanos Konstantinidis (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
Boron trichloride (BCl3) is frequently encountered in plasma surface engineering. Cerium and its compounds have attracted scientific interest as catalytic converters for the reduction of CO emissions in exhaust gases. Moreover, Cerium has been proven to reveal anti-corrosion properties. Two optical spectroscopy methods have been applied to the determination of B-atoms and Ce atom’s absolute densities. A microwave discharge (2.45 GHz) of a surfaguide type is produced in a quartz tube (inner diameter 5 mm) either in Ar - BCl3 gas mixture (process 1) or in pure argon (process 2). In process 2, an Ar - BCl3 gas mixture was introduced downstream of the pure argon plasma. The first method on B-atoms was applied to a remote CVD Ar - BCl3 microwave plasma. At the Ar - l. 5%BCl3 plasma end, the B-atom density nearly reach 1015 cm-3, which corresponds to a BCl3 dissociation degree of about 30%. It was observed the reactions of B-atoms on O2 desorbing from the tube wall after B-atoms collisions. The second optical spectroscopy is the resonant absorption applied to Ce - atoms produced in a DC magnetron sputtering of a Ce cathode. In pure Ar plasmas, the Ce density was 1.5 108 cm-3. By introducing O2 in the Ar plasma, it was observed a hysteresis effect of Ce density as for the plasma voltage.